Engineering crystal phase of Nylon-11 films for ferroelectric device and piezoelectric sensor. (October 2021) - Eom, Kijoo; Na, Sangyun; Kim, Joong-Kwon; Ko, Hyunhyub; Jin, Jungho; Kang, Seok Ju
Abstract: Among non-fluorinated ferroelectric polymers, odd number Nylons have recently attracted attention because of their solution-processibility and decent ferroelectric characteristics. Here, we demonstrate a ferroelectric and piezoelectric Nylon-11 δ` phase crystal film manufactured via a humidity modulated casting and subsequent melt-quenching process. The low relative humidity (RH) below 20% during the spin casting process effectively mitigates the formation of hygroscopic holes resulting in the formation of pin-hole free Nylon-11 thin films. In addition, the subsequent melt-quenching gives rise to the evolution of the ferroelectric δ` phase crystals, which is carefully confirmed by grazing incidence X-ray diffraction and infrared spectroscopy measurements. The resulting ferroelectric thin films show decent remnant polarization of 4.6 μC/cm 2 at a low operating voltage of ±30 V, suggesting the formation of high-quality Nylon-11 δ` phases thin film. Furthermore, the centrifugal casting at low RH facilitates the fabrication of freestanding and transparent 20-μm thick ferroelectric δ` phase film after the subsequent melt-quenching process. The resulting Nylon-11 film provides excellent piezoelectric performance upon external vertical pressure, which enables a proof-of-concept demonstration as a Morse code detector. Graphical Abstract: A facile but strikingly effective approach to fabricating ferroelectric Nylon-11 δ` phase crystal films by a humidity modulated casting and subsequent melt quenching process was demonstrated. Our method allows us to fabricate high-performance ferroelectric capacitors and piezoelectric sensors, exhibiting an excellent remnant polarization and coercive voltage of approximately 4.3 μC/cm 2 and 10 V, respectively. In addition, we demonstrate a piezoelectric-based freestanding 20-μm thick wearable Morse code detector, which can express all of the characters and figures, thus enabling a user to communicate in the form of electronic signals. ga1 Highlights: The high-quality ferroelectric and piezoelectric Nylon-11 δ` phase crystal films were successfully manufactured. The pin-hole-free Nylon-11 thin films exhibited decent ferroelectric characteristics. The freestanding and transparent 20-μm thick Nylon-11 film showed excellent piezoelectric performance upon external vertical pressure.